2015
DOI: 10.1016/j.rbmo.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the seminal plasma proteomes of oligoasthenozoospermic and normozoospermic men

Abstract: A comparative proteomic study of oligoasthenozoospermic and normozoospermic seminal plasmas was conducted to establish differences in protein expression. Oligoasthenozoospermia (when semen presents with a low concentration and reduced motility of spermatozoa) is common in male infertility. Two-dimensional protein maps from seminal plasma samples from 10 men with normozoospermia and 10 men with idiopathic oligoasthenozoospermia were obtained by isoelectric focusing followed by sodium dodecyl-sulphate polyacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 68 publications
3
20
0
3
Order By: Relevance
“…As the first proteomics report regarding the relationship between SP proteome and UMI, the results of the present study indicated that the SP proteome might affect the IVF outcome. All of the differentially expressed proteins which are reported in this study have been reported in the previously published studies as SP proteins (Fung et al, ; Giacomini et al, ; Milardi et al, ). The first differentially expressed protein reported in the present study is clusterin.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As the first proteomics report regarding the relationship between SP proteome and UMI, the results of the present study indicated that the SP proteome might affect the IVF outcome. All of the differentially expressed proteins which are reported in this study have been reported in the previously published studies as SP proteins (Fung et al, ; Giacomini et al, ; Milardi et al, ). The first differentially expressed protein reported in the present study is clusterin.…”
Section: Discussionsupporting
confidence: 65%
“…Wang et al () reported an increase in the NPC2 quantity in the seminal plasma of asthenozoospermic men (Wang et al, ). Interestingly, 3‐ to 4‐fold reduction for NPC2 level has been reported in men with idiopathic oligoasthenozoospermia when compared with normozoospermia (Giacomini et al, ). Sullivan et al () suggested that NPC2 should be involved in the sperm membrane cholesterol efflux (Sullivan et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Using the in-gel digestion based LC-MS/MS approach, Johnston et al identified 1760 sperm proteins [24]. Later on, several other studies also employed the LC-MS/MS-based proteomic profiling of spermatozoa in male infertility cases [9,20,[25][26][27]. In general, comparative protein analysis involves incorporation of stable isotopes for labeling the peptides.…”
Section: Process and Techniquesmentioning
confidence: 99%
“…In the literature, there are several studies that aimed to evaluate the protein composition of seminal fluid of infertile and normal men in order to clarify the mechanisms underlying male infertility (Frapsauce et al ., ; McReynolds et al ., ; Giacomini et al ., ). In the current study, we aimed to compare peripheral blood and seminal fluid SAA protein levels in men classified on the basis of sperm concentration among infertile couples so as to investigate whether SAA protein is an important marker of male infertility.…”
Section: Introductionmentioning
confidence: 97%